Environmental philosophy and good living in university students - Auccatoma-Tinco, Roly (2023)
Environmental philosophy thinks about the death of nature and declares itself against anthropocentric subjectivity. Anthropocentric philosophy with its rational techno-science desacralizes and devastates nature and man. Environmental philosophy is the eco-centric subjectivity that seeks balance and cooperativism between man and nature, fights against androgen and its sexist effect, ethics and science must dignify life; The great leap from anthropocentrism to eco-centrism is possible. The Andean good life is the harmonious coexistence with all living beings: nature, society and with oneself. The objective of this study was to determine the incidence of environmental philosophy to improve the good life of university students; The research approach is quantitative, experimental and the design is pre-experimental with a single pre- and post-test group. The research used the scaling technique and the instrument is Likert scaling. The sample was 25 university students. The result was reached, with the t-Student test, at a value of -6.030 and a p-value of 0.000 < 0.05; It was concluded that environmental philosophy had a significant influence on improving the good life of university students.